DETECTION THE ACCUMULATION OF POLYCYCLIC AROMATIC HYDROCARBONS (PAHs) IN TISSUES OF ARABIBARBUS GRYPUS COLLECTED FROM TIGRIS RIVER , IRAQ - Raghad A.Mustafa; A. J.Al-Rudainy; L .M. Abbas (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The present study was aimed to detect the accumulative effect of polycyclic Aromatic Hydrocarbon (PAHs) in Arabibarbus grypus collecting along the Tigris River Southern of Baghdad City. A total of 130 specimens were taken from three sites in Al-Zafaranyia City from the period between Summer 2020 until Spring 2021.Results of statistical analysis for total PAHs at S3 showed a significant increase (P ≤ 0.05) compared to S1 and S2 for all seasons. Results revealed that the total concentrations of PAHs in both muscles and gills in A.grypus were 57.79, 86.50, 76.90 and 58.20 µg /g during summer, autumn, winter and spring respectively at S1, while at S2 were 83.60, 121.18, 166.90 and 119.90 µg /g during summer, autumn, winter and spring respectively, as well as in S3 the total concentration of PAHs were 139.08, 140.40, 192.70 and 158.80 µg /g during summer, autumn, winter and spring respectively.The highest values of PAHs were recorded during winter at all sites of collection sample either in water or fish, while the lowest values of PAHs were recorded during summer. It can be concluded that the higher concentration of PAHs in fish gills and muscle was recorded at S3 which could be due to its richness of human activities (e.g. industrial, agriculture, urban),have accumulated in sediments which high PAHs compared to S1 and S2.